Родство: стихи / Владимир Емельянов - Емельянов Владимир Иванович (Первая книга в столице, 1984)
Экземпляры: ф.9 (20161117) / Инвентарный номер: 014666 / Цена: 0.20 / Авт.знак: Е 60 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Удм)6